Peranan Kinerja Guru dalam Meningkatkan Prestasi Belajar Siswa Pelajaran Akidah Akhlak Siswa Kelas VIII di MTs. Al-Ahsan - Dahlan, M; Mauludi, Hilmi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the role of teacher performance in improving student achievement in the subject of moral aqidah in class VIII students at MTs. Al-Ahsan Bogor City. This type of research is qualitative research with field research methods or field research. The use of this method is carried out in accordance with the initial purpose of this study, namely to determine the role of teacher performance in improving student achievement in the subjects of aqidah morals class VIII in MTs. Al Ahsan Bogor City. Data collection methods used are observation and interviews. Then, data processing and analysis techniques were carried out using descriptive quantitative analysis techniques. The results of this study indicate that the role of teacher performance is quite good in improving the learning achievement of class VIII students in MTs. Al-Ahsan Bogor City. This can be seen by the existence of a good behavior is evidence that the teacher can attract the attention of students and student achievement in the subject of aqidah morality class VIII in MTs. Al-Ahsan Bogor City can be seen from the level of understanding of the lessons carried out.